2011
DOI: 10.1097/jcn.0b013e3181fb711b
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Responses to Sedative Music in Patients Awaiting Cardiac Catheterization Examination

Abstract: Listening to music resulted in a significantly reduced state of anxiety (P = .003). Both the music and quiet rest groups noted the beneficial effects of decreased HR and increased ST (all P < .001). The treatment effects of both interventions on HR variability were inconclusive. Moreover, we also found that the higher the scores of the music preference, the lower the subjects' perceived anxiety level (P = .05). Our findings provide the necessary scientific support for the use of sedative music and quiet rest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 22 publications
2
48
0
2
Order By: Relevance
“…Treatment of pain with systematic analgesics might require an adequate preprocedural history and physical examination to assure patients receive appropriate agents and dosages for their current condition. In IR settings where this is not done, nurses should be prepared to use nonpharmacologic pain management strategies, such as music therapy, deep breathing and relaxation techniques, or guided imagery (Chair et al, 2012;Chang et al, 2011;Keller et al, 2012;McDaniel et al, 2009;Nikolajsen et al, 2009;Shabanloei et al, 2010;Weeks & Nilsson, 2011;Zakerimoghadam et al, 2010;Zengin et al, 2013). Any of these techniques could also be used in addition to medications.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Treatment of pain with systematic analgesics might require an adequate preprocedural history and physical examination to assure patients receive appropriate agents and dosages for their current condition. In IR settings where this is not done, nurses should be prepared to use nonpharmacologic pain management strategies, such as music therapy, deep breathing and relaxation techniques, or guided imagery (Chair et al, 2012;Chang et al, 2011;Keller et al, 2012;McDaniel et al, 2009;Nikolajsen et al, 2009;Shabanloei et al, 2010;Weeks & Nilsson, 2011;Zakerimoghadam et al, 2010;Zengin et al, 2013). Any of these techniques could also be used in addition to medications.…”
Section: Discussionmentioning
confidence: 96%
“…One study conducted in the cardiac catheterization laboratory setting found that most patients undergoing several procedural types and conscious sedation experienced comfort, whereas a minority (26%) experienced discomfort (Beddoes, Botti, & Duke, 2008). Music, education, and relaxation/massage interventions have been evaluated to decrease pain and anxiety in radiology-assisted procedures (Chair, Chau, Sit, & Wong, 2012;Chang, Peng, Wang, & Lai, 2011;Keller et al, 2012;McDaniel et al, 2009;Nikolajsen, Lyndgaard, Schriver, & Moller, 2009;Shabanloei, Golchin, Esfahani, Dolatkhah, & Rasoulian, 2010;Weeks & Nilsson, 2011;Zakerimoghadam, Shaban, Mehran, & Hashemi, 2010;Zengin et al, 2013); findings are mixed in terms of intervention effectiveness, although most music interventions were effective in reducing pain.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Entre estas alterações estão, aumento da frequência cardíaca 23 e da modulação autonômica cardíaca 24 , além da redução da ansiedade 25 e do aumento da sensação de relaxamento 26 . Estudos explicam que esta influência é percebida por um modelo denominado integração neuro-visceral, onde existe uma interação entre os sistemas de controle da homeostasia que determina o fluxo nervoso autonômico controlador dos órgãos viscerais, levando a alterações em diversas funções fisiológicas 27 .…”
Section: Discussionunclassified
“…50 Music resulted in a significant reduction of anxiety (P = 0.003), and both brief interventions heightened skin temperature and decreased heart rate (P < 0.001), but neither had a significant effect on Hrv. regarding music choices, chinese orchestra music was one of the least favorite selections, and there was a strong, indirect relationship between music preference and anxiety (P = 0.05).…”
Section: Multicultural Applicationsmentioning
confidence: 95%